Dinâmicas sócioeconômicas na prática dos feirantes agricultores familiares de Chapecó-SC - Vasques, Samuel Tafernaberri (2016)
This thesis deals with the insertion of family farmers market that act as market traders in the city of Chapecó, state of Santa Catarina. In order to trust, reciprocity and relations of time and space dynamics present in the practice of open-air market is analyzed. From understanding the outdoor market as an extension of the activities of farms, a form of local construction market, we need new ways to evaluate the inclusion of family farming in trade. In this regard, the importance of local markets characterized by autonomy in the food hegemonic system. To this end, it uses what the peculiarities present in the practice of street fairs, its historical development, the number of farmers who act as market participants, the number of traders in the city and its surroundings, the diversity of products offered, the marketing channel access by traders and market relations farmers who act as market participants. Finally, based on the responses of suppliers and content analysis, it was possible to show how present in the social dynamics of free trade: the trusted face to face representations, reciprocity and relations of time and space between the co-present agents in the market dynamics of family farmers fair. For the study context, these representations show how important non-economic values that help build identities that relate to the strategies of social reproduction and overcoming dominant market model.